Topical Formulation of Nano Spray-Dried Levocetirizine Dihydrochloride against Allergic Edema - Mirella Mirankó; Judit Tóth; Andrea Fodor-Kardos; Krisztina Móricz; Antal Balázs Szenes-Nagy; Attila Gácsi; Tamás Spaits; János Gyenis; Tivadar Feczkó (MDPI AG, 2022)
Levocetirizine dihydrochloride active ingredient was microencapsulated using nano spray-drying technology for preparing microparticles containing topical gel against edema. Hydroxyl propyl methyl cellulose (HPMC) was used as a carrier polymer during spray drying. The active ingredient content of the nano spray-dried products was 52.81% (w/w) and 51.33% (w/w) for ex vivo and in vivo experiments, respectively, and the average particle size was 2.6 µm. X-ray diffraction analysis indicated an amorphous state of the active ingredient embedded in the amorphous matrix of the polymer. Dermal oil gels composed of Miglyol 812 gelated by Dermofeel viscolid included 5% (w/w) (for ex vivo) and 10% (w/w) (for in vivo) active ingredient without or with 0.05% (w/w) menthol penetration enhancer. Qualitative ex vivo penetration studies using a confocal Raman microscopic correlation mapping were executed on human abdominal skin. The results showed that the active ingredient was enriched in the epidermis and upper dermis layer of the skin using oleogel loaded with the nano spray-dried drug-HPMC composite. Menthol addition to the oleogel resulted in the concentration of levocetirizine in the dermis. In vivo tests were performed on a mouse model of croton oil-induced ear edema. Negative control and Fenistil-treated groups were compared using the prepared oil gels with and without menthol. Without penetration enhancer, 20 µL of our oil gel loaded with nano spray-dried levocetirizine dihydrochloride composite showed similar effectiveness to the same volume of Fenistil gel, while 5 µL menthol containing sample was sufficient to eliminate the skin irritation similarly to 20 µL Fenistil.